2020
DOI: 10.1039/d0ja00195c
|View full text |Cite
|
Sign up to set email alerts
|

Plasma modulation using beam shaping to improve signal quality for laser induced breakdown spectroscopy

Abstract: Modulating the laser induced plasma and improving the signal quality of LIBS by beam shaping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This modification reduced the relative standard deviation (RSD) of the Mg I 285.21 nm line in an aluminum magnesium alloy from 33% to 18%. 15 However, these methods require complex equipment and have restricted stability improvements. Consequently, researchers initiate their investigation by analyzing the data and subsequently refining the obtained spectra to enhance their reliability and consistency.…”
Section: Introductionmentioning
confidence: 99%
“…This modification reduced the relative standard deviation (RSD) of the Mg I 285.21 nm line in an aluminum magnesium alloy from 33% to 18%. 15 However, these methods require complex equipment and have restricted stability improvements. Consequently, researchers initiate their investigation by analyzing the data and subsequently refining the obtained spectra to enhance their reliability and consistency.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, the limited measurement repeatability of the system hinders its quantitative analytical performance. Various methods have been developed to improve spectral stability, such as beam shaping, 6 optimization of laser focusing optics, [7][8][9][10] plasma image assistance, 11 algorithm correction, 12,13 etc.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is to improve the experimental equipment or environment. For example, Hou et al 12 improved the LIBS signal quality by shaping the laser beam from a commonly used Gaussian profile to a flat-top profile. Yao et al 13 reported that aberration diminished focusing shrunk the laser focal region, leading to fewer plasma position fluctuations and higher signal repeatability.…”
Section: Introductionmentioning
confidence: 99%